Comment on “An approach to the modeling of honey bee colonies” by Romero-Leiton et al. (2022) - P. Grabowski; P. Grabowski (Web Ecology)
The results of a recent paper on the modeling of a honey bee colony have been supplemented and strengthened by showing that the domain of biological validity of a mathematical model with unstable singularity removed is contained in the domain of attraction of positive stable equilibrium. The results go beyond these of the commented paper.